Are You There, God? It's I, Robot: Examining the Humanity of Androids and Cyborgs Through Young Adult Fiction - Ansusinha, Emily M. (Wake Forest University, 2014)
Technological and biological research is advancing rapidly, and topics previously relegated to science fiction are becoming a reality. Science-fiction novels may in fact be an adolescent's first exposure to topics such as bio-enhancement or artificial intelligence (AI), among others. These novels could be instrumental in determining adolescents' opinions about these topics - coloring the way in which they view or vote on developing technologies. With the goal of postulating about the future societal climate towards robot-human interaction, this thesis examines themes of humanity through the lens of Young Adult (YA) novels featuring android or cyborg protagonists. This thesis presents recent developments in robotics and sets the stage for moral dilemmas that will arise as the technology becomes available to the public. I analyze current societal beliefs about robotic technologies and establish the reasoning for the use of YA literature as a prognostic tool. The primary focus is on which criteria must be met in order to be considered as, or given equal status to, a human person. I question how we ought to treat non-human persons and critique whether the standards are necessary, sufficient, and just.
Keywords: android; artificial intelligence; consciousness; cyborg; emotion; persons